The Application of Fuzzy Time Series Singh for Forecasting Bandwidth Network Demand - Aryanti Aryanti; Ikhtison Mekongga (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
The purpose of this research is to developinformation system which forecast bandwidth network demandby using Fuzzy time series Singh. Data were taken in StatePolytechnic of Sriwijaya during learning hour starting from07.00 am - 06.00 pm from Monday to Saturday in odd semesterof Academic Year 2011/2012. Next, the data were processed byfuzzy time series Singh in order to get forecasted data. Then,the forecasted data were compared to the actual data in orderto get validity of the data. The forecasted data using fuzzy timeseries Singh was nearly precise to the actual data with meanabsolute percentage error of 8.523 %.